Hubungan Iklim Kerja Panas dengan Status Hidrasi Pekerja: Literatur Review - Fedora Ivena Thom; Annis Catur Adi (Universitas Airlangga, 2023)
Background: A hot working climate can result in excessive sweating so that it can cause dehydration in workers if it is not followed by adequate fluid intake. Workers with a hot work environment will interfere with the productivity of these workers. Objectives: The focus of this literature review is to determine the relationship between hot work environments and workers' hydration status. Methods: The journal articles reviewed were acquired from online databases such as science direct and google search without limitation of time and research results. The search for articles began on September 3 – September 15, 2022. Search for articles using the keywords